UMP recognised as hub for TVET automotive - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
SHAH ALAM, 17 June 2022 - Universiti Malaysia Pahang (UMP) received the appointment of the TVET Collaboration Hub in the automotive sector through the Centre for Automotive Engineering UMP in conjunction with the 2022 National TVET Week Closing Ceremony as an effort to realise the current TVET agenda in the country.